2016
DOI: 10.1111/joor.12456
|View full text |Cite
|
Sign up to set email alerts
|

Application of a barometer for assessment of oral functions: Donders space

Abstract: We developed a barometer applicable to a small space, to assess oral and pharyngeal functions. Negative oral pressure during rest and pressure changes during swallowing were measured in a space between the palate and tongue (STP). Twenty volunteers were asked to sit in a chair in a relaxed upright position. A sensor was placed on the posterior midline of hard palate. Recording commenced just before subjects closed their lips and continued. Subjects were asked to swallow saliva and keep the apposition. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…These studies reported a wide range of IPs that varied between −5 and 25 kPa, depending on the performed oral tasks. For instance, a negative IP (−0.5 kPa) occurs in the Donders space with the mandible at rest; swallowing is accompanied by a biphasic baro‐pressure variation with two sequential peaks, varying between 10 and 15 kPa depending on food viscosity; and during the production of the stop consonant /k/, IPs of 2.5, 0.7 and 1.6 kPa occur at the centre of the “Ah” line, at the incisive papilla, and at the mid‐pharynx, respectively . The IP during sound production is lower than that during swallowing .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies reported a wide range of IPs that varied between −5 and 25 kPa, depending on the performed oral tasks. For instance, a negative IP (−0.5 kPa) occurs in the Donders space with the mandible at rest; swallowing is accompanied by a biphasic baro‐pressure variation with two sequential peaks, varying between 10 and 15 kPa depending on food viscosity; and during the production of the stop consonant /k/, IPs of 2.5, 0.7 and 1.6 kPa occur at the centre of the “Ah” line, at the incisive papilla, and at the mid‐pharynx, respectively . The IP during sound production is lower than that during swallowing .…”
Section: Discussionmentioning
confidence: 99%
“…18 The IP during sound production is lower than that during swallowing. [17][18][19] Lastly, IPs higher than the systolic pressure (about 17 kPa) have also been reported. Trumpet players may produce during blowing IPs as high as 25 kPa.…”
Section: Ipmentioning
confidence: 90%
See 2 more Smart Citations
“…We recently developed a novel device using single and/or multiple factory-calibrated miniature transducers to achieve a better understanding of changes in oral pressure in the resting jaw position and during swallowing [14]. This system allows the simultaneous evaluation of baropressure changes at multiple locations.…”
Section: Introductionmentioning
confidence: 99%